Power and Energy Systems Engineering Economics Best Practice Manual - Konstantin, Panos (Springer International Publishing, 2018)
Power and Energy industry is a highly capital intensive business field. Furthermore there is a very close interlinkage between technologies and economics that requires engineers and economists to have a common understanding of project evaluation approaches and methodologies. The book's overall objective is to provide a comprehensive but concise coverage of engineering economics required for techno-economic evaluation of investments in power and energy system projects. Throughout the book, the emphasis is on transferring practical know-how rather than pure theoretical knowledge. This is also demonstrated in numerous examples derived from experience of respective projects. The book comprises seven chapters. The text part is supported by about 25 tables, 40 figures, 55 application examples and 7 Case Studies. Target audience of the book are primarily international consultants, staff members of engineering companies, utility personnel, energy economists and lawyers, as well as employees of government agencies entrusted with regulating the energy and utility sector and, finally, students in related fields of engineering and economics.